Estimating a Bilateral J-curve between the UK and the Euro Area - Michail, Nektarios A. (My University, 2018)
Following the United Kingdom's decision to leave the European Union, the pound has depreciated against the euro. This study aims to examine whether the UK could potentially benefit from this depreciation, that is, improve its trade balance with its euro area counterparts. Theory suggests that this could happen only if the Marshall–Lerner condition holds, i.e. if the sum of import and export elasticities is greater than unity. Due to the fact that the Marshall–Lerner condition is static, a more dynamic estimate, the J-curve, which allows for a distinction between the short-run and the long-run response of the trade balance, is employed using bilateral trade data between the UK and 10-euro area countries. Results, employing both bilateral ARDL and Pooled Mean Group methods show that, until a new trade agreement is reached, the UK trade balance vis-à-vis the euro area is not expected to change significantly in the short-run, while it should improve in the long-run. The wide range of bilateral findings underlies the idiosyncrasies between euro area countries and also suggests that there is a rationale for countries to explore different paths such as bilateral agreements with the UK.
Keywords: UK; Pound; Euro; Marshall–Lerner; J-Curve